Non-synaptic Cell-Autonomous Mechanisms Underlie Neuronal Hyperactivity in a Genetic Model of PIK3CA-Driven Intractable Epilepsy - Roy, Achira; Han, Victor Z.; Bard, Angela M.; Wehle, Devin T.; Smith, Stephen E. P.; Ramirez, Jan-Marino; Kalume, Franck; Millen, Kathleen J. (Frontiers in Molecular Neuroscience, 2021)
Patients harboring mutations in the PI3K-AKT-MTOR pathway-encoding genes often develop a spectrum of neurodevelopmental disorders including epilepsy. A significant proportion remains unresponsive to conventional anti-seizure medications. Understanding mutation-specific pathophysiology is thus critical for molecularly targeted therapies. We previously determined that mouse models expressing a patient-related activating mutation in PIK3CA, encoding the p110α catalytic subunit of phosphoinositide-3-kinase (PI3K), are epileptic and acutely treatable by PI3K inhibition, irrespective of dysmorphology. Here we report the physiological mechanisms underlying this dysregulated neuronal excitability. In vivo, we demonstrate epileptiform events in the Pik3ca mutant hippocampus. By ex vivo analyses, we show that Pik3ca-driven hyperexcitability in hippocampal pyramidal neurons is mediated by changes in multiple non-synaptic, cell-intrinsic properties. Finally, we report that acute inhibition of PI3K or AKT, but not MTOR activity suppresses the intrinsic hyperexcitability of the mutant neurons. These acute mechanisms are distinct from those causing neuronal hyperactivity in other AKT-MTOR epileptic models and define parameters to facilitate the development of new molecularly rational therapeutic interventions for intractable epilepsy.